SYSTEMATIC LITERATURE REVIEW CUSTOMER SATISFACTION WITH ONLINE TRANSPORTATION SERVICES: Systematic Literature Review Customer Satisfaction with Online Transportation Services - Evy Nurmiati; Faiz Rizki Saputra Faiz Rizki Saputra (Indragiri Islamic University, 2024)
Transportation service providers are leveraging advancements in information technology to enhance their online transportation businesses. To stay competitive with other online transportation service providers, these businesses are constantly striving to elevate customer satisfaction. Presently, there is a wealth of research focused on identifying the factors that impact customer satisfaction. Therefore, there is a need for a comprehensive review of journal papers that delve into customer satisfaction in the context of online transportation. This research employs a Systematic Literature Review (SLR) methodology and focuses on journal papers published between 2018 and 2023. The study is guided by three research questions (RQs). The ultimate findings of this research shed light on the most extensively studied applications, which are Go-Jek and Grab. Data collection methods predominantly involve the use of questionnaires, with up to 100 respondents participating. The research highlights that the key driver of customer satisfaction is the quality of service. The insights derived from this study are expected to provide valuable information for operators in the online transportation industry. It is anticipated that this knowledge will encourage these businesses to continually enhance the quality of their services, ultimately leading to increased customer satisfaction and repeated utilization of their services.